2004
DOI: 10.1080/00288233.2004.9513615
|View full text |Cite
|
Sign up to set email alerts
|

Impact of farm‐dairy effluent application on the amounts and forms of phosphorus loss by leaching from irrigated grassland

Abstract: Sufficient evidence exists to support the hypothesis that the eutrophication of surface waters is accelerated by increased transfer of nutrients (e.g., phosphorus, P) from landscape to water. The objective of this paper is to combine the results of a lysimeter experiment that used intact soil monolith lysimeters (50 cm diameter, 70 cm deep) and a field experiment that used field plots (10 × 2 m 2 ) of a Lismore stony silt loam soil (Udic Ustochrept). The soils received mineral P fertiliser alone at 45 kg P ha … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Organic P represented about one‐fifth of total P in leachates and confirmed that this P form was mobile in the soil profile (Toor, Condron, Di, Cameron, & Sims, 2004a, 2004b) with a potential impact on the surface and groundwater systems. Inorganic P accounted for about 80% of the total P in the leachates, and the maximal losses were found in the IP treatment (Figure 3a); the soluble liquid form (KH 2 PO 4 ) in which inorganic P has been supplied could have influenced the dynamics of losses.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Organic P represented about one‐fifth of total P in leachates and confirmed that this P form was mobile in the soil profile (Toor, Condron, Di, Cameron, & Sims, 2004a, 2004b) with a potential impact on the surface and groundwater systems. Inorganic P accounted for about 80% of the total P in the leachates, and the maximal losses were found in the IP treatment (Figure 3a); the soluble liquid form (KH 2 PO 4 ) in which inorganic P has been supplied could have influenced the dynamics of losses.…”
Section: Discussionmentioning
confidence: 53%
“…Interestingly, phytate was reported to reach 29% and 34% of total P in poultry and pig manure, respectively, due to the higher grain component in animal diets and the absence of rumen microflora secreting phytases in monogastric animals (Li et al., 2014). However, when considering leachate from soils receiving dairy farm effluents, organic P forms, either particulate or dissolved, can equal or even exceed inorganic P forms, suggesting that they are less strongly absorbed onto soil colloids and more mobile in the soil profile (Chardon, 1997; Toor, Condron, Di, Cameron, & Sims, 2004a, 2004b). The increasing agricultural practice of applying manure/slurry on arable or permanent crops can result in the accumulation of surplus P in soils characterized by high agronomic P status and/or in P losses with a potential impact on the surface and groundwater systems (Schoumans et al., 2014).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Toor et al . () measured losses of 0.3‐2.3 kg P/ha over two years deeper than 0.7 m below the ground surface. There is much overseas data to show that P is mobile in aquifers comprised of sand and alluvial gravels due to high transmissivity, potential for bypass flow, and low P sorption capacity (Stollenwerk, ; Corbet et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…It is common practice to irrigate FDE onto pastoral land to recycle the nutrients, making FDE an economically valuable resource for dairy farms (Di et al, 1998, 1999; Laubach et al, 2015; Minogue et al, 2010). However, research has shown that when FDE is applied onto shallow free‐draining soils or soils with artificial agricultural drainage systems, there is a high risk of phosphate (P) being transferred into surface waters and groundwater (Cameron & Di, 2019; Houlbrooke & Monaghan, 2009; McDowell et al, 2019; Monaghan & Smith, 2004; Toor, Condron, Cade‐Menun, et al, 2004; Toor, Condron, Di, et al, 2004). Figure 1 illustrates how FDE is applied to land over a subsurface tile drain system.…”
Section: Introductionmentioning
confidence: 99%